Legal Protection for Doctors in the Use of Robotic and Telerobotic Surgical Devices: Reconstruction of Distributed Causal Liability - Fachri Razi; Handar Subhandi Baktiar; Abdul Kolib (International Journal of Social Sciences and Humanities, 2026)
The development of health technology based on robotics, artificial intelligence, and digital telecommunication systems has encouraged the use of robotic and telerobotic surgical devices in medical procedures. These technologies improve surgical precision, expand access to specialist services, and strengthen the digital transformation of health care. However, their use also raises new legal issues, particularly regarding the limits of physician liability when patient harm results from system failure, network disruption, software error, or robotic device malfunction. This article analyzes the current legal framework for robotic and telerobotic surgical devices in Indonesia and formulates a legal protection model for physicians. This study applies normative legal research using statutory, conceptual, and comparative approaches. The findings show that Law Number 17 of 2023 concerning Health, Government Regulation Number 28 of 2024, and Minister of Health Regulation Number 3 of 2025 have not specifically regulated robotic surgery and telerobotic surgery. As a result, the distribution of liability among physicians, hospitals, technology providers, system operators, and medical device manufacturers remains normatively unclear. This article recommends the adoption of specific regulation and the implementation of the Tiered and Distributed Causal Liability Model, so that legal responsibility can be allocated proportionally based on the source of error, degree of control, and causal contribution of each actor.